Comparative Analysis of Teachers’ Discipline and Control in Public and Private Secondary Schools in Lagos State, Nigeria - Olatunde Olaide Atanda; Lydiah Wambugu (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This paper examined the different approaches in teachers’ discipline and control in public and private secondary schools in Lagos State, Nigeria. The population of this descriptive study were 3000 teachers drawn from all the six education districts of Lagos State. The sample consisted of 1200 teachers drawn using multistage sampling procedure. Descriptive and inferential statistics tools were used to analyse the data gathered. Descriptive statistical methods such as frequency counts and percentages were used to answer the research questions while an inferential statistic of T-test was employed to test the hypotheses at 0.05 alpha level of significance. The study revealed that approaches of teachers’ discipline in public secondary schools are quite relaxed and easy from the approaches used in private secondary schools which are quite harsh. Also, the study revealed that the form of indiscipline among teachers in both public and private secondary schools in Lagos state are different. While the leaving the school before the closing time is mostly found in public schools, form of trading among teachers is the predominately form indiscipline in private secondary. The study recommended that teachers should strictly adhere to the school ethics as this will curb indiscipline in the school and also attend professional training, seminal or symposium to update their skills regularly.